3 - Actualité de la pensée économique de Karl Marx et analyse de la crise économique africaine: by Pana Ewihn-Liba - Pana Ewihn-Liba, (Africa Development, 1997)
The value of Karl Marx's work dwells, for modem economists, inter alia, in the didactic and methodical values that allowed him construct the dialectical movement law which commands the evolution of the economies of societies. Ideas tracing back from Marx are echoed in the social and economic debate of the centre capitalist countries and their peripheiy. Politicians and commentators are not quoting Marx, but they often confront issues that generally were not recognised as such before him, namely unequal development, due to the pursuit of maximum profit, is one of the system factors that generated long theoretical debates. It now practically corresponds to global scale political oppositions in terms of «North-South» relationships.